2017
DOI: 10.1016/j.jplph.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing soybean photosynthetic CO 2 assimilation using a cyanobacterial membrane protein, ictB

Abstract: Soybean C photosynthesis can suffer a severe loss in efficiency due to photorespiration and the lack of a carbon concentrating mechanism (CCM) such as those present in other plant species or cyanobacteria. Transgenic soybean (Glycine max cv. Thorne) plants constitutively expressing cyanobacterial ictB (inorganic carbon transporter B) gene were generated using Agrobacterium-mediated transformation. Although more recent data suggest that ictB does not actively transport HCO3-/CO, there is nevertheless mounting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…However, they could barely survive at ambient levels of atmospheric CO 2 thus showing that other components of the cyanobacterial CCM were necessary for efficient CO 2 fixation in C 3 plants. In contrast, transfer of the cyanobacterial inorganic carbon transporter B (IctB) enhanced biomass accumulation in a variety of plant species, including A. thaliana , tobacco, rice, and soybean . Transfer of the C. reinhardtii putative inorganic carbon transporters LCIA and HLA3 as GFP fusions into A. thaliana resulted in growth comparable with that of wild‐type plants …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they could barely survive at ambient levels of atmospheric CO 2 thus showing that other components of the cyanobacterial CCM were necessary for efficient CO 2 fixation in C 3 plants. In contrast, transfer of the cyanobacterial inorganic carbon transporter B (IctB) enhanced biomass accumulation in a variety of plant species, including A. thaliana , tobacco, rice, and soybean . Transfer of the C. reinhardtii putative inorganic carbon transporters LCIA and HLA3 as GFP fusions into A. thaliana resulted in growth comparable with that of wild‐type plants …”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported in transgenic A. thaliana and potato plants when a photorespiratory bypass was engineered in the chloroplast. Recently, simultaneous overexpression of the photorespiration pathway enzyme glycine decarboxylase‐H protein and the two Calvin‐Benson cycle enzymes sedoheptulose 1,7‐bisphosphatase (SBPase) and fructose 1,6‐bisphophate aldolase also led to a cumulative impact on photosynthesis, carbon assimilation and yield Similarly, the expression of ictB in soybean chloroplasts led to significantly more efficient photosynthetic CO 2 assimilation and greater biomass accumulation …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the overexpression of native enzymes ( Figure 1 ), a number of studies have also shown effects through the expression of foreign membrane transporter proteins in both model 59 , 67 69 and crop species such as soybean and rice 70 , 71 . These genes derived from cyanobacteria include the frequently studied but functionally-unknown membrane transporter protein IctB 72 .…”
Section: Calvin-benson Cycle Optimizationmentioning
confidence: 99%
“…In contrast with plants bearing a cyanobacterial RuBisCO enzyme (Lin et al 2014a;Long et al 2018), the enhancements in photosynthetic rates seen in Arabidopsis, tobacco and rice ictB transgenic lines were observed at ambient [CO 2 ], but not very short-term exposure to saturating [CO 2 ] during photosynthetic assessments (Lieman-Hurwitz et al 2003;Gong et al 2015). However, in the case of soybean, ameliorations in aboveground dry weight biomass and seed yield compared to wild type were apparent under field conditions at both ambient and long-term exposure (more than 5 weeks) to e[CO 2 ] (~ 600 ppm; Tables 1, 2; Hay et al 2017).…”
Section: Introduction Of Carbon-concentrating Mechanismsmentioning
confidence: 96%
“…Intriguingly, transgenic plants heterologously expressing a single cyanobacterial inorganic carbon transporter B (ictB) gene, which encodes a transporter that does not appear to actively transport HCO 3 − or CO 2 , have been shown to exhibit significant increases in light-saturated photosynthetic rates and growth (Lieman-Hurwitz et al 2003;Gong et al 2015;Hay et al 2017), although it is possible that at least in certain cases these improvements may be limited to low humidity conditions (Lieman-Hurwitz et al 2003). While the precise function of ictB has yet to be elucidated, it has been suggested that its introduction into a C 3 plant may alter internal membranes in such a manner that facilitates the diffusion of CO 2 from intercellular air spaces to RuBisCO, allowing for higher enzyme activity (Hay et al 2017). In contrast with plants bearing a cyanobacterial RuBisCO enzyme (Lin et al 2014a;Long et al 2018), the enhancements in photosynthetic rates seen in Arabidopsis, tobacco and rice ictB transgenic lines were observed at ambient [CO 2 ], but not very short-term exposure to saturating [CO 2 ] during photosynthetic assessments (Lieman-Hurwitz et al 2003;Gong et al 2015).…”
Section: Introduction Of Carbon-concentrating Mechanismsmentioning
confidence: 99%